An overview of current advancements in pancreatic islet transplantation into the omentum. Issue 5 (3rd September 2021) - Damyar, Kimia; Farahmand, Vesta; Whaley, David; Alexander, Michael; Lakey, Jonathan R. T.
ABSTRACT: Pancreatic islet transplantation to restore insulin production in Type 1 Diabetes Mellitus patients is commonly performed by infusion of islets into the hepatic portal system. However, the risk of portal vein thrombosis or elevation of portal pressure after transplantation introduces challenges to this procedure. Thus, alternative sites have been investigated, among which the omentum represents an ideal candidate. The surgical site is easily accessible, and the tissue is highly vascularized with a large surface area for metabolic exchange. Furthermore, the ability of the omentum to host large volumes of islets represents an intriguing if not ideal site for encapsulated islet transplantation. Research on the safety and efficacy of the omentum as a transplant site focuses on the utilization of biologic scaffolds or encapsulation of islets in a biocompatible semi-permeable membrane. Currently, more clinical trials are required to better characterize the safety and efficacy of islet transplantation into the omentum.